2016
DOI: 10.1242/dmm.026435
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis: identifying and characterising polymorphisms using rat models

Abstract: Rheumatoid arthritis is a chronic inflammatory joint disorder characterised by erosive inflammation of the articular cartilage and by destruction of the synovial joints. It is regulated by both genetic and environmental factors, and, currently, there is no preventative treatment or cure for this disease. Genome-wide association studies have identified ∼100 new loci associated with rheumatoid arthritis, in addition to the already known locus within the major histocompatibility complex II region. However, togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 126 publications
2
23
0
Order By: Relevance
“…Traditional quantitative trait locus studies, with the need for lengthy fine-mapping and testing of candidate genes, continue to give valuable insights (for example Zhao et al, 2015; Fernandez-Duenas et al, 2015; Wang et al, 2016, and reviewed in Yau and Holmdahl, 2016), but, as with research using other model organisms, these approaches are being replaced by gene targeting using CRISPR/Cas9 and other techniques, as exemplified by the GERRC programme () and the osteocalcin study in this issue (Lambert et al, 2016). These programmes use gene targeting to knock out genes implicated in the aetiology of common human diseases via genome-wide association studies (GWAS) or other patient-based studies, and allow analysis of gene function that will give insights into disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional quantitative trait locus studies, with the need for lengthy fine-mapping and testing of candidate genes, continue to give valuable insights (for example Zhao et al, 2015; Fernandez-Duenas et al, 2015; Wang et al, 2016, and reviewed in Yau and Holmdahl, 2016), but, as with research using other model organisms, these approaches are being replaced by gene targeting using CRISPR/Cas9 and other techniques, as exemplified by the GERRC programme () and the osteocalcin study in this issue (Lambert et al, 2016). These programmes use gene targeting to knock out genes implicated in the aetiology of common human diseases via genome-wide association studies (GWAS) or other patient-based studies, and allow analysis of gene function that will give insights into disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A second Review in this issue, contributed by Anthony Yau and Rikard Holmdahl, describes arthritis-associated genetic polymorphisms that have been identified by genetic linkage and positional cloning using rat congenic strains (Yau and Holmdahl, 2016). The authors provide examples to illustrate how exploration of arthritis-linked polymorphisms using rats has provided new insights that are relevant to clinical autoimmune arthritis.…”
Section: Frontrunners: Reviews and Morementioning
confidence: 99%
“…It is believed that the development of RA is triggered by complex interactions between genetic and environmental factors 5 . The common environmental factors include smoking, female, and oral contraceptive use 6 . Moreover, previous studies have suggested that genetic factors may account for approximately one-half to two-thirds of the risk of RA 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A T‐cell‐driven arthritis model that is not dependent on the administration of exogenous Ags is pristane‐induced arthritis (PIA) in the rat . Pristane is a saturated, naturally occurring, hydrocarbon that is used for ascites production and the induction of lupus in mice .…”
Section: Introductionmentioning
confidence: 99%